Cost Benefit Analysis (CBA) of Semarang - Solo Toll Road Infrastructure Development - Christy Elisha, Lempira; Soesilowati, Etty; Setyadharma, Andryan (Journal of Economic Education, 2021)
The economic growth of Central Java Province in the fourth quarter of 2018 - the first quarter of 2019 experienced a slowdown. During this period, the economic growth in the Java region also showed a slowdown, namely in the first quarter of 2019 by 5.66% (yoy). The economic growth of Central Java Province in the first quarter of 2019 was recorded at 5.14% (yoy). The use of the Public Private Partnership (PPP) concept can be seen as an opportunity to improve the quality of expense both at the Central Government and in the Regional Government. This study aims to analyze the Public private partnership model and the costs as well as benefits of providing the Semarang - Solo toll road infrastructure. The method used in this research was mixed methods. The research results show that The form of cooperation for Semarang-Solo Toll Road is Build Operate Transfer (BOT), the actors of the collaboration are PT Jasa Marga (Persero) Tbk, PT Astra Infra and PT SPJT (PT. Sarana Pembangunan Central Java). Management time for 45 years with a higher Return On Investment (ROI) value in 2018 reaching 6.61%, the better the construction of Semarang-Solo toll road infrastructure and this affects the payback period of investment, which is 7 years.